The Involvement of Danger-Associated Molecular Patterns in the Development of Immunoparalysis in Cardiac Arrest Patients - Timmermans, Kim; Kox, Matthijs; Gerretsen, Jelle; Peters, Esther; Scheffer, Gert Jan; van der Hoeven, Johannes G; Pickkers, Peter; Hoedemaekers, Cornelia W (Critical care medicine, 2015)
After cardiac arrest, patients are highly vulnerable toward infections, possibly due to a suppressed state of the immune system called "immunoparalysis." We investigated if immunoparalysis develops following cardiac arrest and whether the release of danger-associated molecular patterns could be involved. Observational study. ICU of a university medical center. Fourteen post-cardiac arrest patients treated with mild therapeutic hypothermia for 24 hours and 11 control subjects. Plasma cytokines showed highest levels within 24 hours after cardiac arrest and decreased during the next 2 days. By contrast, ex vivo production of cytokines interleukin-6, tumor necrosis factor-α, and interleukin-10 by lipopolysaccharide-stimulated leukocytes was severely impaired compared with control subjects, with most profound effects observed at day 0, and only partially recovering afterward. Compared with incubation at 37°C, incubation at 32°C resulted in higher interleukin-6 and lower interleukin-10 production by lipopolysaccharide-stimulated leukocytes of control subjects, but not of patients. Plasma nuclear DNA, used as a marker for general danger-associated molecular pattern release, and the specific danger-associated molecular patterns (EN-RAGE and heat shock protein 70) were substantially higher in patients at days 0 and 1 compared with control subjects. Furthermore, plasma heat shock protein 70 levels were negatively correlated with ex vivo production of inflammatory mediators interleukin-6, tumor necrosis factor-α, and interleukin-10. Extracellular newly identified receptor for advanced glycation end products-binding protein levels only showed a significant negative correlation with ex vivo production of interleukin-6 and tumor necrosis factor-α and a borderline significant inverse correlation with interleukin-10. No significant correlations were observed between plasma nuclear DNA levels and ex vivo cytokine production. None. Release of danger-associated molecular patterns during the first days after cardiac arrest is associated with the development of immunoparalysis. This could explain the increased susceptibility toward infections in cardiac arrest patients.